IMPLEMENTASI PENDIDIKAN KEWARGANEGARAAN DI PERGURUAN TINGGI - Hamidah Hamidah (FORUM PAEDAGOGIK, 2019)
The background of Civic Education appearance is started with the long history of the Indonesian nation which began from the struggle and defense of independence until the completion of independence even continued until the reform era. The spirit of the nation's struggle which is a spiritual mental force has released tremendous strength in the physical struggle. Moreover in facing globalization and the future to fill independence requires a non-physical struggle in accordance with their respective fields of profession. The non-physical struggle requires a means of educational activities for every Indonesian citizen in general and students as prospective scholars in particular, namely through Civic Education.